Tool for assessing ecosystem services in Bamboo forests in Colombia - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The tools describes a step-wise approach to assessing multiple ecosystem services in natural bamboo forests as well as bamboo agroforestry systems. Examples of the application in such systems in Colombia are presented.